Digitalisasi Konsep Mawaddah Wa Rahmah dalam Al-Qur’an dan Hadist: Strategi Psikologi Keluarga untuk Membangun Keharmonisan Rumah Tangga di Desa Bucor Wetan Probolinggo - Dewi Shinta Kurnia Ilahi; Ainur Rofiq Sofa (Jurnal Budi Pekerti Agama Islam, 2025)
This study examines the digitalization of the concept of Mawaddah wa Rahmah in the Qur'an and Hadith as a family psychology strategy to build harmonious households in Bucor Wetan Village, Probolinggo Regency. With a population of approximately 4,000 people, the village faces challenges in applying the values of love and mercy in daily family life. The research employs a qualitative method with a phenomenological approach, involving in-depth interviews, direct observations, and document analysis. The findings reveal that digitalization through Islamic value-based educational media, such as interactive videos and family education applications, plays a significant role in raising public awareness of the importance of Mawaddah wa Rahmah. These digital media are effective in improving communication patterns, managing conflicts, and strengthening relationships among family members. Despite challenges such as limited internet access and digital literacy, training programs conducted during the research helped address these obstacles. The study concludes that integrating Islamic values with digital technology can be an innovative and effective solution for creating harmonious and prosperous families. This approach facilitates social transformation that supports peaceful family life, especially in rural communities like Bucor Wetan Village.